Detection of diabetic metabolism disorders post‐mortem – forensic case reports on cause of death hyperglycaemia. Issue 9 (25th April 2013) - Hess, C.; Wöllner, K.; Musshoff, F.; Madea, B.
Abstract : Diabetic coma is the most severe form of hyperglycaemic metabolic disorders. The post‐mortem diagnosis of this disorder of glucose metabolism can be difficult and vague due to a lack of characteristic morphological findings. Six death cases caused by diabetic coma are described with special focus on biochemical (and histological) findings. The possible glycaemia markers glucose, lactate, HbA1c, fructosamine, anhydroglucitol, and ketone bodies were measured and the usefulness of these parameters is evaluated and discussed. Estimations of glucose concentrations in vitreous humour or cerebrospinal fluid and of ketone bodies in blood or other matrices are obligatory while measurements of HbA1c, fructosamine, or anhydroglucitol can only provide additional information on the long‐term adjustment of diabetes in the deceased. Lactate concentrations (addition of glucose and lactate levels to form the sum formula of Traub) do not give more information than the glucose concentration itself and can be therefore omitted. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Six death cases caused by diabetic coma are described with special focus on biochemical (and histological) findings. Estimations of glucose concentrations in vitreous humour or cerebrospinal fluid and of ketone bodies in blood or other matrices is obligatory while measurements of HbA1c, fructosamine or anhydroglucitol can only provide additional information on the long‐term adjustment of diabetes in the deceased.